Long-term spatio-temporal trends in extreme wave events in the Niger delta coastlines. - Osinowo, Ayodotun Adekunle; Popoola, Samuel Olatunde (ELSEVIER , Continental Shelf Research, 2021)
Wave climate in the marginal seas and estuaries provide baseline information, risk assessments and essential insight into coastal design, structure and engineering projects. This paper investigates the Spatio-temporal trends in extreme Significant Wave Height (SWH) in the Niger Delta coastlines. For the study domain, European Centre for Medium-Range Weather Forecasts (ECMWF) global atmospheric reanalysis ERA-Interim and wave hindcast data covering 37 years (January 1, 1980–December 31, 2016), derived from WAVEWATCH III (WW3) model were used in the analysis. The largest 99th percentile approach was used to analyze extreme SWH values. Results showed near neutral and negative trends over the region. The trends are generally insignificant for the 100-year return period. The sharp variation in extreme SWH between 1998 and 2000 resulted from a strong El Nino and La Nina phenomenon, which is associated with the weakening and strengthening of the West-African Monsoon.
Continental Shelf Research, 224, 104471.
Keywords: Wave Climate; Extreme SWH; Spatio-temporal trend; WAVEWATCH III; Niger Delta coastlines; ACECOR